KEMAMPUAN KONEKSI MATEMATIS SISWA SMP PADA MATERI LINGKARAN - Hasna Zuyyina; Tommy Tanu Wijaya; Helmy Muhammad P; Eka Senjawati (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2018)
This research aim to learn and analyze the capability of student’s mathematical connection in circle major. The data collected are instrumen test result and interview result with several student’s who are chosen randomly. The method of this research use qualitative descriptive method. The population of this research are second grade student’s of Junior High School in Madani Boarding School West Bandung. Based on the capability of mathematical connection test result the first indicator are finding relation among various representation concept and prosedure, then aunderstanding the relation in mathematic topic, the presentage are 41%. While the second indicator are understanding the representation of the same equivalen concept, the presentage are 70%. The third indicator presentage, use math in others study field or in daily life. Each presentage are 23%, 21%, 43%, and 35%. Meanwhile for the fourth indicator, use the evaluate the connection between math topic with the topic outside are 95%. Beside that interview result show some of difficulties faced by student’s in doing mathematical connection problem are 1) can’t understanding what the purpose of the question, 2) confuse with the formula that should be used, 3) error in using arithmatic operation.Keyword : mathematical connection, circle